Transtorno de déficit de atenção/hiperatividade em escolares de São José do Rio Preto e categorização de publicações sobre o tema - Darim, Naiara Perin (2016)
Attention Deficit Hyperactivity Disorder (ADHD) is the most discussed learning disorder in the last decade; Its prevalence and the consumption of the medicines for its treatment have been increasing. Goals: The goals of this study were to evaluate the prevalence of Attention Deficit Hyperactivity Disorder at São José do Rio Preto’s schools and to organize the publications on ADHD made in the last decade by Brazilian psychologists. Method: To collect data on ADHD in the city, all schools that agreed to participate in the survey were visited and answered a questionnaire; To categorize the publications of psychologists a research was done in the main online journals, and among those, the selected were read and categorized. Results: Of the 250 schools in São José do Rio Preto, 181 (72%) participated in the study, which reached a total of 62,899 students. The prevalence of students diagnosed with ADHD was 1.32%, and of students receiving methylphenidate 1.2%. There were a higher number of students diagnosed with ADHD in private schools. Among the medicated students, 89 were under the age of 6, which contradicts the indication of usage of this kind of medication. About the categorization of publications, 203 publications were selected and organized. Conclusions: According to the data collected, the report of ADHD in schools in São José do Rio Preto was 1.32% and methylphenidate use was reported in 1.2% of cases; A considerable number of children under 6 years of age using the drug were found. With the categorization of the publications it became clear that the majority of the researches are of field, the area of psychology more approached is Neuropsychology and that the orientations of the Federal Council of Psychology on avoiding the pathologization and medicalization of childhood are part of several researches of the category about the subject.